Impact of Strategic Leadership on Organizational Wellbeing A Study Based on Sri Lanka Police - Ratnayake, S.B.D.C. (NPRC Journal of Multidisciplinary Research, 2025)
This study examines the impact of strategic leadership on organizational well-being, using the Sri Lanka Police as a case study. Strategic leadership plays a crucial role in fostering organizational success, particularly in complex and dynamic environments. The research explores key dimensions of strategic leadership, including alignment, decision-making and interpretation, and their effects on financial, social and human resource well-being. The study employed a qualitative research methodology, utilizing thematic analysis to identify the relationships among variables. The findings indicate a significant positive relationship between strategic leadership and organizational well-being, particularly in terms of social and human resource well-being. Based on these findings, the study recommends strengthening leadership development programs, implementing participatory leadership approaches and establishing structured frameworks to address external changes. Policymakers and law enforcement agencies can utilize these insights to refine leadership models and enhance organizational resilience. This research contributes to the existing literature by providing empirical evidence on the interplay between strategic leadership and organizational well-being in a public sector institution, emphasizing the need for adaptability and proactive leadership in managing external uncertainties.